Comparative Effects of Recombinant Staphylokinase and Streptokinase on Platelet Aggregation - Abdelouahed, Mustapha; Hatmi, Mohamed; Helft, Gérard; Emadi, Sharareh; Elalamy, Ismaïl; Samama, Meyer Michel (Thrombosis and Haemostasis, 1997)
Recombinant staphylokinase (RSTA) has been shown to offer promise as a thrombolytic agent. In contrast to streptokinase (SK), few studies have been devoted to possible effects of RSTA on platelets. We have compared the capacity of RSTA and SK to trigger platelet aggregation and to modify ADP (2.5 µM) response in platelet-rich plasma (PRP) of 25 healthy subjects. Thus, exposure of PRP to SK (40 to 50 µg/ml) induced platelet aggregation in 6 out of 25 subjects. However, under the same conditions, RSTA failed to induce platelet aggregation in all cases (25 out of 25 subjects). In contrast to RSTA, SK (0.4 to 50 µg/ml) greatly reduced ADP-induced platelet aggregation in 12 out of 25 subjects. Preincubation of plasma with SK is associated with a decrease in the fibrinogen concentration. Furthermore, there was a good correlation between SK-induced fibrinogenolysis and SK- induced platelet aggregation defect (r2 = 0.9; p = 0.001). No fibrino genolysis was observed when different amounts of RSTA (0.4 to 50 µg/ml) were incubated in plasma for one min. However, there was a marked decrease in fibrinogen level (about 50%) when the plasma was incubated for five min with a very high concentration of RSTA. SK markedly enhanced the platelet response to ADP in 13 out of 25 subjects. In PRP of 6 out of 25 subjects, SK induces platelet aggregation and potentiates platelet response to ADP, however in PRP of 7 out of 25 subjects, SK caused only the increase of platelet response to ADP. The monoclonal antibody anti-FcγRIIal, IV-3 (2 [µ/ml), abolished SK-induced platelet aggregation and SK-enhanced ADP-induced platelet aggregation. In all cases (25 out of 25 subjects), RSTA failed to potentiate platelet response to ADP.These findings confirm that RSTA has a lesser fibrinogenolytic ability than SK and suggest its negligeable effect on platelet function.